'Heteroglossia in IsiXhosa/English bilingual children's writing: a case study of Grade 6 IsiXhosa Home Language in a Township School - Matutu, Samkelo Nelson (School of Education, 2021)
The South African constitution recognises 11 official languages, of which isiXhosa is one. IsiXhosa belongs to the Nguni language family which also comprises of isiZulu, isiNdebele, and siSwati. IsiXhosa is mostly spoken in the Eastern and Western Cape Provinces. Those that regard isiXhosa as their home language (HL) are referred to as amaXhosa. However, as a teacher of isiXhosa HL, I have observed that there is often a mismatch between the isiXhosa used by the students and the one used in the schooling context. Thus, this study explores and investigates the written language varieties Grade 6 isiXhosa HL students use in their formally assessed and informal writing. The theoretical framework used in this study reviews literature on discourse/language and literacy as social practice, language ideologies and identity, heteroglossic and translingual practices, as well as primary school children's writing in South Africa to understand the complexities of students' language varieties. Moreover, this study explores the way in which the isiXhosa HL students represent their varied language resources through use of a language body portrait. Further, issues of language standardisation in relation to children's literacy are also reviewed. This study takes the form of qualitative case study in design. Students' Formal Assessment Task (FATs), language body portrait and informal paragraph writing about their linguistic repertoire were collected and analysed. Data analysis revealed the following themes: language ideologies, linguistic repertoires, use of urban and everyday language varieties, Standard Written isiXhosa (orthography), language borrowings, as well as unconventional spellings. Themes and categories are intensively analysed in Chapters four and five of this study. This study displays evidence of hybridity and fluidity of named languages, as well as heteroglossic practices that the students employ. Analysing the students' writing was effective in helping understand how bi/multilinguals engage in writing and that, while the adopted curriculum approach to language and FAT is monoglossic, children's writing is heteroglossic (see also Bakhtin, 1981; Krause and Prinsloo, 2016). The implications of teaching languages as bounded, fixed and separate entities are explored and problematized. Chapter six of this study concludes the study and offers recommendations that are important for deliberation when teaching writing in isiXhosa/African language contexts.